Impact of sports enjoyment on academic resilience among student-athletes - Aries Pasno (Physical Education of Students)
Background and Study Aim. Previous studies have shown that students who enjoy participating in sports can improve their resilience in academic endeavors. However, such studies are predominantly conducted internationally. Few, if any, focus on the Philippine higher education setting. This study aimed to determine the direct influence of sports enjoyment on academic resilience. Material and Methods. The respondents in this study are student-athletes from different sports events, currently enrolled in the 1st Semester of the Academic Year 2023-2024 at Bulacan State University in the Philippines. Data were collected using an online survey questionnaire administered via Google Forms. This study employed three separate questionnaires. The first questionnaire gathered demographic characteristics of the respondents. The second part used the Physical Activity Enjoyment Scale-8 (PACES-8). The final part consisted of the Academic Resilience Scale-30 (ARS-30). The relationship between sports enjoyment and academic resilience was measured using Pearson-r. To determine the direct influence of sports enjoyment on academic resilience, simple linear regression was performed. Results. The findings indicate a positive and significant relationship between the two variables [r(299) = .435, p < .05]. This suggests that when athletes derive great pleasure from their sporting activities, their ability to persevere academically is enhanced. Thus, engaging in sports helps students overcome difficulties in their educational setting and improves their academic achievement. Additionally, sports enjoyment (SE) predicts academic resilience (ARS). This indicates that SE has a direct influence on ARS [F(1, 229) = 53.528, p < .001]. The R² = .189 suggests that the model accounts for 18.9% of the variance in ARS.